Indirect magneto-ionic effect in FeSi2/Si nanocomposite induced by electrochemical lithiation and delithiation - M Prasch; R Würschum; S Topolovec (JPhys Materials, 2024)
A nanocomposite consisting of iron disilicide nanocrystals embedded in a Si matrix was prepared from industry-grade ferrosilicon by ball milling and subsequent heat treatment. By tailoring the heat treatment temperature either the metallic α -FeSi _2 or the semiconducting β -FeSi _2 phase could be made the dominant one, as indicated by x-ray diffraction. Magnetization curve and zero-field cooled/field cooled measurements revealed that ferromagnetic and superparamagnetic centers are present in the nanocomposites, which could be attributed to Fe-rich defective regions at the surface of the iron disilicide nanocrystals. For both nanocomposites, containing either mainly the α or β phase, we could show that the magnetization can be varied by about 40% by electrochemical lithiation and delithiation of the surrounding Si matrix, with up to 6.5% of the magnetization change being reversible. These variations could be attributed to the formation of additional Fe-rich magnetic regions, induced by a local change of the Fe/Si fraction at the FeSi _2 /Si interfaces, and their subsequent partial elimination. Thus, this work demonstrates a new concept for how an ‘indirect magneto-ionic effect’ can be obtained in composite materials consisting of a phase prone to the electrochemical ion uptake (i.e. the Si matrix) and a magnetic phase (i.e. the FeSi _2 nanocrystals).